Evaluation of high school-based dengue solution model in Southern Thailand: a community participatory action research - Suwanbamrung, Charuai; Mehraj, Sandeep Kumar; Kercho, Melkamu Worku; Stanikzai, Muhammad Haroon; Ageru, Temesgen Anjulo; Jaroenpool, Jiraporn; Pibul, Panatda; Shohaimi, Shamarina; Israel, Eskinder (Springer Nature, 2024)
Introduction: By the time the globe started to tackle the COVID-19 pandemic, Southeast Asian countries had faced an increased dengue incidence, which has eventually become an important public health problem. However, effective and sustainable disease control measures in the area are still lacking. Therefore, the current study is aimed to evaluate the development and implementation of high school-based dengue solution model in Southern Thailand. Methods: Integrated community participatory action research (CPAR) was employed using preparation, planning, implementation, and evaluation. Data was collected using quantitative and qualitative methods from high school students. Descriptive statistics such as frequency and percentage, chi-square and fisher’s exact test were used to summarize and compare quantitative data before and after intervention. Similarly, qualitative data was collected through interviews and focus group discussion (FGD) and then analyzed through thematic analysis. Results: Two hundred and thirty-nine (96.3%, n = 239/248) and 232 (93.5, n = 232/248) participants were included in the interventions before and after, respectively. School-based dengue prevention was developed with input from a variety of stakeholders, including students, community leaders, health educators, district officials, and community health volunteers. As demonstrated by pre- to post-test results, students understanding of dengue and the larval indices surveillance system has increased. Students who received the training were not only inspired but created a sense of community responsibility with a high commitment to teaching and sharing information in their circle to enhance overall community wellbeing. Being female and higher educational attainment was associated with students understanding of dengue and larval indices surveillance. Conclusion: This participatory action research not only improved students' understanding of dengue but also empowered them to be proactive in various community health initiatives. The positive correlation between educational attainment and students understanding of dengue solution and larval indices surveillance underscores the need for tailored educational interventions that address diverse learning needs within the community. Collaborative efforts to establish dengue health information center based at primary schools and above can better improve reduction of dengue incidence.